Evaluation of the regulatory effect of Chrysoperla externa on whitefly Trialeurodes vaporariorum in tomato - Castro L., Mayerly Alejandra; Martínez O., John Wilson; Dotor R., Mónica Yadira (Revista de Ciencias Agrícolas, 2016)
Tomato (Solanum lycopersicum L) is one of the most important vegetable crops in Colombia. Among the limiting factors to tomato crops, whitefly Trialeurodes vaporariorum Westwood (Hemíptera: Aleyrodidae) seems to be one of the most important. The objective of this study was to evaluate, under laboratory conditions, the regulatory capacity of Chrysoperla externa Hagen (Neuroptera: Chrysopidae) (predator) on T. vaporariorum. Leaflets nymphs (prey). Preys were obtained from tomato plants infested with T. vaporariorum and then placed into plastic containers with covers. Thereafter, one individual of the predator, in first, second or third instar, was introduced. We use prey densities of 50, 75 and 100 individuals for the first and second larval instar of the predator and 100, 150 and 200 individuals for the third larval instar. We added a control with 50 individuals without predator. A complete randomized experimental design was used with five replicates, with 17.8 ºC and 67.5% of relative humidity. There were statistical differences between prey densities in all instars. In the first instar mortality percentages were 96.8%, 80.5% and 56.4%, and in the second were 94.4%, 77.5% and 75.4%, to 50, 75 and 100 preys, respectively. On the other hand, the third larval instar showed 99.1 %, 90% y 76.6% mortalities. According to the results, C. externa exhibited a regulatory effect, showing II type functional response for all three larval instars evaluated.